2022
DOI: 10.3390/electronics11030484
|View full text |Cite
|
Sign up to set email alerts
|

Driver Cardiovascular Disease Detection Using Seismocardiogram

Abstract: This article deals with the treatment and application of cardiac biosignals, an excited accelerometer, and a gyroscope in the prevention of accidents on the road. Previously conducted studies say that the seismocardiogram is a measure of cardiac microvibration signals that allows for detecting rhythms, heart valve opening and closing disorders, and monitoring of patients' breathing. This article refers to the seismocardiogram hypothesis that the measurements of a seismocardiogram could be used to identify driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This article is closely related to the previous article of this research group, and will continue the work of improving the quality of the study of nonclinical SCG signals [35]. Also, the work relates to investigations of using wireless sensors and them effective energy consumption [36][37][38].…”
Section: R = 8lµmentioning
confidence: 85%
“…This article is closely related to the previous article of this research group, and will continue the work of improving the quality of the study of nonclinical SCG signals [35]. Also, the work relates to investigations of using wireless sensors and them effective energy consumption [36][37][38].…”
Section: R = 8lµmentioning
confidence: 85%
“…The wearability of our proposed system has the advantage of higher accuracy, along with the disadvantage of being slightly intrusive for the driver, while camera-based solutions are contactless and independent from the driver. To solve the problem of intrusiveness, non-wearable biological sensors have been presented in the literature, for instance, sensors integrated in the driver’s seat such as capacitive electrocardiogram (cECG), Ballistocardiogram (BCG) [ 50 , 51 ], Seismocardiogram (SCG) [ 52 ], or steering wheel ECG [ 53 ], or radar systems [ 54 ]. However, compared to wearable bio-sensors they have less efficiency and accuracy and are more prone to being affected by other environmental conditions such as humidity, vibration, and the driver’s clothing [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laurin et al [28] demonstrated the reliability of HRV indices derived from SCG signals, and Tadi et al [29] confirmed a strong association between HRV indices derived from ECG and SCG. Beyond traditional ECG applications, MCG signals have proven effective in classifying cardiovascular anomalies through smartphones [1], [30], estimating respiratory rate (RR) [12], [31], determining tidal volume alongside ECG from SCG [32], estimating cardiac time intervals from SCG [33], real-time cardiovascular disease detection for drivers [34], among other applications. Thus, based on the aforementioned discussions, ECG estimated from MCG components possesses the capability to detect and classify cardiac anomalies in non-healthy patients in advanced applications.…”
Section: Introductionmentioning
confidence: 99%